Green spaces and Human Rights: to an environmental justice in urban space: espaços verdes e Direitos Humanos: para uma justiça ambiental em espaço urbano - Vidal, Diogo Guedes (2019)
Cities must be pleasant and healthy spaces able to contribute to ecosystems regeneration and to bring closer Humans and Nature. Increase urbanization carries socioenvironmental challenges that may be tackled by promoting green spaces as safeguarders of sustainability and of the connection between users and the biosphere. Cities are unequal spaces regarding the distribution of available resources and infrastructures (Bourdieu 1993, Maia 2003, Tilly, 2005, Therborn, 2006, Massey, 2007, Costa, 2012). The 11th goal of the 2030 Agenda for Sustainable Development states that societies must ensure universal access to safe, inclusive and fully accessible public spaces. The production and reproduction of space is a competition process for the physical and symbolic space which results in the creation of socio-economic clusters within the cities, with cities emerging within the city. The fair distribution of urban green spaces must be ensured in both quantity and quality in terms of ecological, social or health promotion services. The concept of Environmental Justice assumes that all individuals, regardless of their social, cultural or economic condition, should have the right to a fair treatment and to get involved in the development, implementation and enforcement of environmental regulations and policies (Lawson, 2008). This communication aims to reflect on the distribution and quality of green spaces in the city of Porto and on how their presence may contribute to environmental justice. The city of Porto does not offer an equitable distribution of green spaces that takes into account its population mosaic. In areas of greater socio-economic deprivation and vulnerable to environmental problems, it is observable that the quantity and quality of green areas is much lower when compared to other socially and economically favoured areas of the city.